2021
DOI: 10.1021/acs.cgd.1c00664
|View full text |Cite
|
Sign up to set email alerts
|

Fivefold Helical Cellulose Trapped in a Sulfuric Acid Framework

Abstract: Sulfuric acid aqueous solution effectively dissolves cellulose at a concentration of 64 wt% when it is pre-cooled at -20 ˚C. Although this low-temperature acid solution has a high potential as an aqueous cellulose solvent, the molecular detail of its swelling and dissolution mechanism is not known. In this study, we followed the swelling behavior of cellulose in sulfuric acid using X-ray diffraction and found a crystalline complex of cellulose and sulfuric acid at -20 ˚C. In this structure, the sulfuric acid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…However, the peaks did not match those of ZnCl 2 or other zinc salts generated in the solution (Figure S5). Similar sharp peaks from the swollen cellulose structure have also been reported for cellulose in ionic liquids and sulfuric acid, suggesting that the swollen structures are crystalline complexes of cellulose and the swollen agents. The sharp peaks observed for ZnCl 2 swollen phase I are ascribed to the complex structure of cellulose chains and ZnCl 2 .…”
Section: Resultssupporting
confidence: 76%
“…However, the peaks did not match those of ZnCl 2 or other zinc salts generated in the solution (Figure S5). Similar sharp peaks from the swollen cellulose structure have also been reported for cellulose in ionic liquids and sulfuric acid, suggesting that the swollen structures are crystalline complexes of cellulose and the swollen agents. The sharp peaks observed for ZnCl 2 swollen phase I are ascribed to the complex structure of cellulose chains and ZnCl 2 .…”
Section: Resultssupporting
confidence: 76%
“…These observations are in striking contrast with the cellulose-sulfuric acid complex, whose radial width of reflections were significantly narrower than the original cellulose Iβ. We attributed this apparent increase of crystallite size in the sulfuric acid complex to the increase in the interchain distance of cellulose due to the incorporation of sulfuric acid molecules in the crystalline lattice (Li et al 2022). Although its unit cell is significantly smaller than the sulfuric acid complex, the interchain distance also increased in the phosphoric acid complex compared to cellulose Iβ.…”
Section: Crystal Structure Of Cellulose-phosphoric Acid Complexmentioning
confidence: 93%
“…The complexation of cellulose and sulfuric acid occurs only at low temperatures, and cellulose molecules adopt a rare five-fold helical conformation (five glucose residues in two turns, or n=2.5) in the complex structure. Such a structure was not without precedent; earlier work with the gelling molecule xanthan had shown that its cellulose backbone could apparently form both single-and double-helices with each strand having the n=2.5 conformation (French and Johnson, 2004;Moffat et al 2016;Morris 2019).The complexation was likely driven by the deficiency of water around sulfuric acid molecules that recruit cellulose hydroxyl groups to form a stable hydrate-like structure (Li et al 2022). This finding prompted us further to explore the complexation behavior of cellulose and mineral acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several structures of relatively simple crystallosolvates, such as cellulose-amine complexes, have been reported [56,57], many crystallosolvates with larger and more complex guest molecules are yet to be studied. Improved experimental data have become available for many such structures in recent years [16,58,59]. They are, however, not yet producing reliable molecular models due to the high degree of freedom and dynamic nature of the system and the lack of an established method to explore all the potential molecular arrangements.…”
Section: Current Challenges and Future Directions In Polysaccharide C...mentioning
confidence: 99%